Tracheocarotid artery fistula in a patient who had tracheostomy successfully treated with a saphenous vein graft. Issue 3 (29th March 2021) - Dahill, Katherine Elizabeth; Dempsey, Ged
Abstract : Tracheoarterial fistula is a complication of tracheostomy with a high associated mortality. A 25-year-old male patient with Duchenne's muscular dystrophy underwent a percutaneous tracheostomy using the single tapered dilator (Blue Rhino) technique to facilitate weaning from mechanical ventilation. Nine weeks after the procedure, he developed significant upper airway bleeding, leading to haemodynamic instability. A CT angiogram of the neck and thorax did not reveal a source of the bleeding. The patient was subsequently transferred to the operating theatre where a 1 cm defect in the right common carotid artery was found and repaired with a graft from the left short saphenous vein. Clinicians who undertake tracheostomy formation should be aware of the possibility of tracheoarterial defect and may wish to discuss it at tracheostomy formation. It should be considered early in the event of a significant bleed. This case identifies deep tissue infection and misplacement of the tracheostomy tube as major contributing factors to fistula formation.